(untitled) - Bradley, Hoffmann (Boston, 2007)
"Applied Calculus for Business, Economics, and the Social and Life Sciences, Expanded Edition" introduces calculus in real-world contexts and provides a sound, intuitive understanding of the basic concepts students need as they pursue careers in business, the life sciences, and the social sciences. This expanded edition includes four additional chapters on Differential Equations, Infinite Series and Taylor Approximations, Probability, and Trigonometric Functions. The new ninth edition builds on the straightforward writing style, practical applications from a variety of disciplines, clear step-by-step problem solving techniques, and comprehensive exercise sets that have been hallmarks of Hoffmann/Bradley's success through the years.
Keywords: Calculus; Textbooks